Association of ABO blood group and leptin level on Framingham risk score in determining cardiovascular disease risk - Md Noor, Sabariah; Abdullah, Nurul Izzati; Kahar, Fitri; Abd Malek, Fatin Syazwani; Eusof Izzudin, Md Parvez; Idris, Faridah; Bahari, Hasnah; Shariff Ghazali, Sazlina; Mohamad Amin, Amrina (Universiti Putra Malaysia Press, 2024)
Introduction: Cardiovascular diseases (CVD) remain the leading cause of mortality globally. Blood group antigens have been associated with increased susceptibility to diseases, especially CVD. Leptin offers significant potential to improve the accuracy of CVD risk prediction. Framingham Risk Score (FRS) is the standard risk assessment tool for estimating the 10-year CVD. This study aims to determine the association of ABO blood and leptin level with FRS in assessing CVD risk. Materials and methods: A cross-sectional study was conducted among 431 patients without CVD aged from 30-75 years. Blood samples were analyzed for the ABO blood group using antigen-antibody aggluti- nation, and plasma leptin levels were measured using magnetic Luminex with a functional sandwich immunoassay. FRS calculation was categorized into low and moderate-high-risk groups. Results: Patients’ median (IQR) age was 56 (19) years. Most were females (59.4%), Malays (72.6%), non-diabetic (63.8%), hypertensive (53.1%), dyslipidemia (79.8%), non-O blood group (60.6%), rhesus-positive (99.3%) and the moderate-high-risk group of FRS (66.8%). ABO blood group and leptin levels were found not significantly associated with FRS. However, the use of anti-dys- lipidemia agents (AOR = 6.44, 95% CI: 2.72–15.26, p < 0.001) and fasting blood sugar (FBS) levels (AOR = 1.75, 95% CI: 1.18–2.62, p = 0.006) were significantly associated with moderate-to-high FRS risk. Conclusion: While non-O blood group and leptin levels were prevalent, neither was associated with FRS. In contrast, anti-dyslipidemia medication use and elevated FBS levels showed strong associations with moderate-to-high FRS risk, emphasizing the importance of managing dyslipidemia and blood sugar in reducing cardiovascular risk